Determinants of Maritime English Proficiency in Vocational Higher Education: The Roles of Self-Directed Learning, Simulation-Based Training, and Educational Culture - Sri Purwantini; Adhi Pratistha Silen; Syafni Yelvi Siska (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2026)
Maritime English is a critical competence in vocational maritime education because it supports safe communication, operational performance, and global employability. However, empirical evidence regarding the combined influence of self-directed learning, simulation-based training, and educational culture on Maritime English proficiency remains limited. This study investigated the effects of self-directed learning and simulation-based training on Maritime English proficiency, as well as the moderating role of educational culture among students at Politeknik Ilmu Pelayaran Semarang. Using an explanatory quantitative design, data were collected from 444 students through a five-point Likert-scale questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that self-directed learning and simulation-based training significantly improve Maritime English proficiency, with simulation-based training emerging as the strongest predictor. Educational culture also demonstrates a significant direct contribution to Maritime English proficiency. However, educational culture does not significantly moderate the relationships between self-directed learning, simulation-based training, and Maritime English proficiency. These findings highlight the importance of contextual simulation practices and autonomous learning development in strengthening Maritime English competence within vocational maritime education. The study contributes to vocational language education literature by integrating learner autonomy, simulation-based learning, and institutional culture within a single predictive model.